2013
DOI: 10.1007/s11104-013-1737-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of variability in the structure and recruitment of rhizospheric and endophytic bacterial communities associated with arable sweet sorghum (Sorghum bicolor (L) Moench)

Abstract: (167 words)Sorghum is the second most cultivated crop in Africa and is a staple food source of many African communities. Exploiting the associated plant growth promoting bacteria (PGPB) has potential as an agricultural biotechnology strategy to enhance sorghum growth, yield and nutritional properties. Here we use Terminal-Restriction Fragment Length Polymorphism (T-RFLP) and Denaturing Gradient Gel Electrophoresis (DGGE) to evaluate the factors that potentially shape rhizospheric and endophytic bacterial commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
3
11
0
2
Order By: Relevance
“…However, in this study, sorghum stem communities were slightly more diverse than sorghum root communities. This further supports the hypothesis that only a small proportion of sorghum-associated endophytic bacteria are specifically recruited to different niches, whereas the bulk of the endophytic community is composed of opportunistic endophytes that are subjected to minimal selective pressure (Ramond et al, 2013). Dominant phylotypes in sorghum included ecologically and biotechnologically significant bacterial genera.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, in this study, sorghum stem communities were slightly more diverse than sorghum root communities. This further supports the hypothesis that only a small proportion of sorghum-associated endophytic bacteria are specifically recruited to different niches, whereas the bulk of the endophytic community is composed of opportunistic endophytes that are subjected to minimal selective pressure (Ramond et al, 2013). Dominant phylotypes in sorghum included ecologically and biotechnologically significant bacterial genera.…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that the DNA extraction procedure introduces significant bias, thereby influencing the interpretation of the microbial community observed. PCR-based metagenomic approaches such as DGGE Ramond et al, 2013), t-RFLP (Sessitsch et al, 2012;Ding et al, 2013) and next generation sequencing (Gottel et al, 2011;Lucero et al, 2011;Ìnceoğlu et al, 2011;Molina et al, 2012) are continuously used to elucidate the structure and ecological roles of plant-associated (and other) microbial communities. However, few, if any, of these studies share the same DNA extraction protocol and/or are preceded by an evaluation of DNA extraction procedures to select the most efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, geographic location and soil characteristics are the main factors explaining the variability in the structure of the bacterial community in the rhizosphere of sorghum [9]. Moreover, in an earlier study, we found soil to be the most important factor on sorghum rhizosphere bacterial community assembly followed by plant growth stage and plant genotype [10].…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been made towards the establishment of model host–microbiome systems for the legume Medicago [42], Populus [43], rice [13,15,44–46], Sorghum [47], Miscanthus [48], maize [49,50], and tomato [51]. All of these model organisms have fully sequenced genomes and growing communities of researchers to extend their utility for microbiome research.…”
Section: Research Prioritiesmentioning
confidence: 99%